Comparative analysis of labor productivity factors of personnel of medical organizations providing care to patients with cardiovascular diseases - A. N. Popsuyko; E. A. Morozova; G. V. Artamonova (Вестник университета)
The issues of improving efficiency of health care institutions are increasingly becoming the center of scientific discussions. The purpose of the study is to examine the subjective assessments of medical organizations staff regarding factors of labor productivity. Objectives of the study: to analyze the existing approaches to the study of labor productivity factors of medical personnel, to study the opinion of medical organizations staff regarding labor productivity factors, to identify the most significant of them, and to conduct a comparative analysis of the data obtained in the course of sociological research in medical organizations providing medical care to patients with cardiovascular diseases in the Kemerovo Region – Kuzbass. The authors have studied the conclusions and findings of selected foreign and domestic experts in this field of research. The presented study identifies the key factors that can increase labor productivity of all categories of personnel on the example of two medical institutions providing care to patients with cardiovascular diseases, namely: presence of a system of material (non-material) incentives, level of material and technical support, moral and psychological climate, working conditions, and regular professional development. Common and special features of two organizations have been shown. Differences in assessing labor productivity factors in different professional categories have been found. The results obtained can be used as a basis for improving personnel policy in direction of increasing labor productivity in health care and medical science institutions.